PENGARUH MOTIVASI KERJA INTRINSIK DAN MOTIVASI KERJA EKSTRINSIK TERHADAP KINERJA KARYAWAN (STUDI PADA PT. ANGKASA PURA I BANDAR UDARA INTERNASIONAL AHMAD YANI SEMARANG) - Linawati, Linawati (KINERJA, 2014)
Work motivation is one of the important factors that can influence dan improve of employees’ performance. This research is intended to analyze the influence of intrinsic work and extrinsic work motivation on the performance of the employees. The respondents consist of 60 employees of PT. Angkasa Pura I in Ahmad Yani International Airport, Semarang. The questionnaires are used to collect data from the respondents. Forty five (45) items of the questionnaires are used to measure the variable of intrinsic work motivation, extrinsic work motivation and performance of the respondents. The data were analized with multiple regression analysis. The result of the study indicates that: (i) intrinsic work motivation and extrinsic work motivation has positive significant influence on the employees’ performance (ii) intrinsic work motivation has no dominant influence on the employees’ performance.Keywords: intrinsic work motivation, extrinsic work motivation, employees’ performance